Efficacy of seed pre-treatments on seed vigour index with exogenous jasmonic acid and salicylic acid to mitigate pathogen-induced stress in mungbean selected genotypes in India - Rayanoothala, Pravallika Sree; Sri Veda, Desetty JMSNK; Mahapatra, Sunita; Das, Srikanta (Plant Science Today, 2024)
Our agriculture is threatened by resource depletion, biodiversity loss, and climate change. A new agricultural revolution is necessary to increase crop productivity and sustainably ensure food quality and safety. SA and JA were used to prime seeds, which can assist in assuring the long-term viability of agriculture. Seed elicitor priming is a potent method for altering the metabolic and signalling pathways in seeds, which impacts the whole plant life cycle, not only germination and seedling establishment. A few advantages include higher nutritional quality of food, greater output, and improved plant growth and development. The effects of elicitor priming on metabolic pathways and the balance of reactive oxygen species and plant growth hormones increase stress and disease tolerance while lowering the need for pesticides and fertilizers. To evaluate seed vigour, shoot weight, shoot height and germination % were employed. Indicating that pre-sowing treatments can have either positive or negative effects on seed vigour depending on the treatment dose, the use of SA and JA in combination as an elicitor had a marginally advantageous impact on seed vigour. More studies are required to determine their effects and the ideal seed priming dosage.